Analysis of the Effect of Frequency Variation on the Speed of a Single-Phase Induction Motor - Jon Timo Bariman M; Solly Aryza; Beni Satria (Sean Institute, 2025)
Single-phase induction motors are widely used in domestic and light industrial applications, but their performance is often affected by variations in power supply frequency, which affect rotor speed, torque, and energy efficiency. This study aims to analyze in depth the effect of frequency on the performance of a single-phase induction motor through an experimental approach, focusing on the relationship between frequency, rotor speed, torque, and energy efficiency. Tests were conducted on a 1 horsepower motor using a variable frequency drive at a frequency range of 30 to 70 hertz. Rotor speed (in revolutions per minute), torque (in newton-meters), and energy efficiency (in percent) were measured under no-load and mechanically loaded conditions. The results show that the rotor speed increases linearly from 820 revolutions per minute at 30 hertz to 1850 revolutions per minute at 70 hertz under loaded conditions. Torque peaks at 2.30 newton-meters at 50 hertz, while energy efficiency increases from 21.18% at 30 hertz to 40.00% at 70 hertz. This research provides a model of the relationship between frequency and motor performance that can be used to optimize motor operation in practical applications, especially to improve energy efficiency in the domestic and light industrial sectors.